DESAKRALISASI OTORITAS KEAGAMAAN TUAN GURU PURIFIKASI SALAFI VERSUS TRADISIONALISME NAHDLATUL WATHAN - Saparudin Saparudin (Khazanah: Jurnal Studi Islam dan Humaniora, 2022)
This study aims to analyze the traditional Islamic practice of Nahdlatul Wathan (NW) in positioning and attaching the religious authority of Tuan Guru or Kyai, which is being challenged by the Salafi purification movement. This also determines the efforts needed to desacralize this authority by the Salafi elite who united by the perception that the sacredness of certain people, including Tuan Guru, is unknown in Islam, and even contradicts Islamic teachings with claims based on the salaf manhaj. Data collected was based on the phenomena from the ideological contestation at the elite level of the two religious groups that affect the pattern of religion and the internal interaction of religious people in Lombok. It was then analyzed using the contestation theory framework operationally formulated by Antje Winner. Based on empirical tendencies, the result showed that the desacralization of religious authority is not solely influenced by theological factors of religious understanding rather by the struggle for the religious authority of religious elites in the public sphere. This indicates the increase in the number of Salafi preachers who carry the purification theme in various mosques and Majlis Taklim, the higher the probability of seeing educational institutions as a new challenge for Tuan Guru to maintain religious authority. The implication is that there is social fragmentation and conflict involving sectarian sentiments of religious groups, where the contestation of religious elites contributes.